Attachment style and psychological adjustment in couples - Conde, Ana (2011)
The present study addresses the gap in research concerning poor marital support together with insecure attachment style explaining risk for anxiety or depression in both members of a couple expecting a baby. The Attachment Style Interview (ASI) was administered separately to both members of a couple (N ¼ 126) during the second trimester of pregnancy together with measures of state-anxiety (STAI-S) and depression (EPDS). These measures were repeated at three months postpartum. While insecure attachment style was related to higher anxiety and depression symptoms in both partners at both time periods, there was an increase of postnatal depression symptoms in women. Poor partner support contributed to anxiety symptoms only in men. When insecure attachment combinations in both members of the couple were examined, insecure styles increased anxiety and depression symptoms in both genders antenatally, but postnatal anxiety symptoms only in women. A combined effect of partner’s support and attachment style on temporal changes of anxiety symptoms was observed differently for women and men. It is important to assess attachment style and partner support of both members, as well as the mutual interplay between them, to understand gendered differences in psychological adjustment of a couple expecting a baby.